The effects of adding carrots and pineapples on fruit leather acceptance - Indah Budiarti; Rachmawati (JAND: Journal of Applied Nutrition and Dietetic, 2021)
Fruit leather is dried sweet in the form of thin sheets with a thickness of about 2-3 mm and a moisture content of 10-25%. Moreover, fruit leather has a typical consistency and taste of fruit. Fruit leather is generally made of fruit. However, carrot pulp is still rarely used as an ingredient of fruit leather. This study aimed to determine the effects of adding carrots and pineapple pulp on the 30 panelists’ acceptance in fruit peels with three formulas: F1 = 37.5% carrots pulp and 62.5% pineapples; F2 = 50% carrots pulp and 50% pineapples; and F3 = 62.5% carrots pulp and 37.5% pineapples. The organoleptic test revealed that the skin color of F1 and F2 fruits were preferred by most of the panelists while the skin color of F3 fruit was moderately preferred by the panelists. The taste of F1 fruit leather was preferred by most of the panelists, while the taste of F2 and F3 fruit leathers were moderately preferred by the panelists. Furthermore, the smell of the F1 fruit leather was moderately preferred by the panelists while those of F2 and F3 were preferred by most of the panelists. The fruit leather textures of F1 and F2 fruit leathers were preferred by most of the panelists while the texture of F3 fruit leather was moderately preferred by the panelists. To conclude, the addition of carrot and pineapple flesh significantly affected the colors of the fruit skin but not its taste, smell, and texture. This study recommends using a different drying medium, such as an oven to speed up the drying process.